PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR TEKNOLOGI INFORMASI DAN KOMUNIKASI SISW KELAS III SD JAMIYYATUL HUJJAJ BUKITTINGGI - Nurafni; Khairuddin; Hari Antoni Musril; Sarwo Derta (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the learning process of Information and Communication Technology where educators tend to only explain everything to students, or only with print media. The tendency of learning that is less attractive to students is a natural thing. However, if this continues to be applied, it will have an unfavorable impact on student learning outcomes. So it is necessary to make an update in the learning process using video media. Video is the medium used in this research, video is a set of media that is capable of displaying both images and sound at the same time. This study aims to determine how much influence the use of learning videos has on student learning outcomes in the subjects studied by the researchers, namely Information and Communication Technology. The method used in this study uses a quantitative approach with a quasi-experimental research method. The research was conducted at Jami'yyatul Hujjaj Elementary School, Bukittinggi. The population is class III SD and the sample is class IIIB as the experimental class and class IIIC. The instrument used in the form of multiple choice test, and prerequisite analysis using normality test, homogeneity, t test, with the hypothesis using SPSS version 2.0. The results of the research that have been carried out there are differences between the prettest value and the posttest value, from the t-test value on the posttest data, the value thit = 130.19 > ttab = 0.348 with a comparison level of 0.05 then H1 is accepted and H0 is rejected. So from the statement value thit = 130.19 > ttab = 0.348 then this hypothesis test is accepted. So it can be concluded that there is a significant effect of this learning video on the learning outcomes of Information and Communication Technology. Keywords: Video Media, Learning Outcomes, ICT